EFL Students’ Academic Procrastination in Indonesian Context - Yusuf, David Ilham; Femilia, Praptika Septi (Journal of Language Intelligence and Culture, 2022)
Many studies have been written about students’ academic procrastination. Yet, not many wrote specifically about EFL context. This study tried to fill the gap, especially in Indonesian context where English is officially taught as a foreign language. The study aims to examine the level of EFL students’ academic procrastination; the reasons of doing the procrastination; and the correlation of students’ procrastination level with their academic achievement especially for reading and writing skill. It was conducted by applying quantitative approach with descriptive quantitative and correlation research design. A hundred and eighty seventh semester students of a State Islamic University in Indonesia was the population for this study, while 35 students of which were chosen randomly as the samples. A five-scale questionnaire was applied to collect the data, and then the result was analyzed quantitatively by using descriptive and Spearman formula on SPPS 26. The findings showed that the students’ level of procrastination was moderate; the students inclined doing the procrastination in the area of sincerity and aversiveness of task; and there was no significant correlation between procrastination and writing as well as reading achievement.